2018
DOI: 10.1111/birt.12389
|View full text |Cite
|
Sign up to set email alerts
|

Infection and wound breakdown in spontaneous second‐degree perineal tears: An exploratory mixed methods study

Abstract: Although second-degree tears were common after vaginal birth, wound infection/breakdown was relatively uncommon. Women who report feeling unwell or develop pyrexia postnatally should be assessed urgently. A prospective longitudinal study exploring the long-term sequelae of second-degree tears is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…A qualitative study on the experiences of women revealed that some obstetric professionals do not adequately assess or guide their patients with perineal trauma on the proper care and this lack of guidance causes continuous psychological suffering in puerperal women. Therefore, developing research in this area is important to understand the multidimensional aspects involved in perineal trauma (Wiseman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study on the experiences of women revealed that some obstetric professionals do not adequately assess or guide their patients with perineal trauma on the proper care and this lack of guidance causes continuous psychological suffering in puerperal women. Therefore, developing research in this area is important to understand the multidimensional aspects involved in perineal trauma (Wiseman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…31 Microbes implicated in wound infection include species of streptococci, staphylococci, Gramnegative enteric bacteria and anaerobes, although normal flora have also been recovered from wound swabs. 93 One case of toxic shock syndrome caused by methicillin-resistant Staphylococcus aureus (MRSA) in a perineal infection has been reported. 94 Further research is warranted particularly in the sphere of wound assessment.…”
Section: Infections Associated With Perineal Tears and Episiotomymentioning
confidence: 99%
“…Проведені проспективні дослідження показали, що інфікування рани після епізіотомії ускладнювало перебіг післяпологового періоду у 10% жінок, тоді як рани після розриву промежини 1-го ступеня -лише у 2% випадків [8,9]. Додатковими клініко-анатомічними факторами ризику післяпологової перинеальної інфекції є розріз по серединній лінії (перінеотомія), розрив 3-го чи 4-го ступеня, «продовження» епізіотомії в розрив, неушиті розриви промежини та піхви [10][11][12].…”
Section: вступunclassified